Comprehensive handbook of multicultural school psychology - Frisby, Craig L. (John Wiley & Sons, 2005)
The Comprehensive Handbook of Multicultural School Psychology highlights the latest research in this area and offers practical information on integrating issues of cultural diversity into research and practice.